Coralline Ba/Ca ratios and luminescent line records in Con Dao Island, offshore Vietnam, as indicators of Mekong river runoff between 1948 and 1999 - Phong, Dang Xuan (Vietnam Journal of Earth Sciences, 2014)
The Ba/Ca ratios and luminescent lines recorded in coral skeleton in near-shore corals are reflected by fresh river flows. This paper shows 52-year Ba/Ca ratios and bright luminescent lines recorded  in coral Porites  in the Con Dao Island area, offshore Vietnam, about 90 km from the mouth of the Mekong River. Bright luminescent lines and Ba/Ca ratios are cyclical and formed annually, where the brightluminescent lines and the highest Ba/Ca ratios are simultaneously formed. The measured Mekong River discharge (MRD) and salinity data recorded during the 1985-1999 period show that the annual maximum MRD and minimum salinity in Con Dao Island were synchronous, and that the annual maximum Ba/Ca ratio was formed during maximum MRD and minimum salinity. When the annual minimum MRD and salinity were stable,  the annual minimum Ba/Ca ratio was variable. Overall, the mean annual MRD and Ba/Ca ratio slightly decreased during the 1985-1999 period, suggesting that the Ba/Ca ratio is mainly controlled by MRD. The decreasing trend in Ba/Ca ratios over the period between 1948 and 1999  is probably related to the MRD reduction due to human activities and/or climate change.References Alibert, C., Kinsley, L., Fallon, J.S., McCulloch, M.T., Berkelmans, R., McAllister, F., 2003: Source of trace element variability in Great Barrier Reef corals affected by the Burderkin flood plumes. Geochim. Cosmochim Acta. 67, 231-246. Barnes, D.J. and Taylor, R.B., 2001: Natural and artificial luminescence in a skeletal slice of Porites. Coral Reefs 19, 270. Boto, K. and Isdale, P., 1985: Florescent bands in massive corals result from terrestrial fulvic acid inputs to the near shore zone. Nature. 315, 396-397. Dang, X.P., Mitsuguchi, T., Kitagawa, H., Uchida, T., Shibata, Y., 2006: Sr/Ca ratio of Porites coral from Con Dao Island, South of Vietnam. Proc. of 10th International Coral Reef Symposium, 567-571. Dang, X.P., Mitsuguchi, T., Kitagawa, H., Shibata, Y., Kobayashi, T., 2004: Marine reservoir correction in the south of Vietnam estimated from an annually-banked coral. Radiocarbon. 46, 657-660. Dunbar, R.B., 1995: The Tropical Influence on Global Climate, Are Surprises the Rule? EOS October 24, 1995. Fang, L.S. and Chou, Y.C., 1992: Concentration of fulvic acid in the growth bands of hermatypic corals in relation to local precipitation. Coral Reef. 11, 187-191. Fine, R.A., Lukas, R., Bingham, F.M., Warner, M.J., Gammon, R.H., 1994: The western equatorial Pacific, a water mass crossroads. J Geophys Res. 99, 25,063-25,080. Gordon, A.L., 1986: When is “appearance” reality? Indonesian flow through is primarily derived from N. Pacific water masses. J. Geophys Res. (Ocean) 25, 1560-1567. Le, T.V.H., Nguyen, H.N., Volanski, E., Tran, T.C., Haruyama, S., 2007: The combined impact on the flooding in Vietnam’s Mekong River delta of local man-made structure, sea level rise, and dams upstream in the river catchment. Estuary Coastal Shelf Sci 71(1-2), 110-116. Levitus S, Burgett R, Boyer TP, 1994: World ocean atlas volume 3, salinity NOAA Atlas NESDIS 3 Washington DC, US Department of Commerce. Lu, X.X and Siew, R.Y., 2006: Water discharge and sediment flux changes over the past decades in the Lower Mekong River: possible impacts of the Chinese dams. Hydrol. Earth Syst. Sci. 10, 181-195. Hendy, E.J., Gagan, M.K., Lough, J.M., 2003: Chronological control of coral records using luminescent lines and evidence for non-stationary ENSO teleconnections in northeast Australia. The Holocene. 13, 187-199. Isdale, P.J., 1984: Fluorescent bands in massive corals record centuries of coastal rainfall. Nature . 310, 578-579. Isdale, P.J., 1995: Coral rain gauges, the proxy fluorescence record in massive corals-a discussion paper, In Paleoclimate and environmental variability in the Austral-Asian transect during the past 2000 years. Proc 1995 Nagoya IGBP_PAGE/PEP-II Symposium, 51-59. Isdale, P.J., Stewart, B.J., Lough, J.M., 1998:  Palaeohydrological variation in a tropical river catchments, a reconstruction using fluorescent bands in corals of the Great Barrier Reef, Australia. The Holocene  8, 1-8. Jones, G. , 1990: Environmental assessment of a coral core to record phosphorus and trace element pollution in Cleveland Bay preliminary investigations. Final Report December 1990, Townsville/Thuringgowa Water Board, Queensland, 33. Kummu, M and Varis, O., 2007: Sediment-related impacts due to upstream reservoir trapping, the Lower Mekong River. Geomorphology85. 275-293. Konishi, K., Tanaka, T., Sakanoue, M., 1982: Secular variation of radiocarbon concentration in seawater. Proc 4th Int Coral Reef Symp 2, 181-185. Lea, D.W., Boyle, E.A., Shen, G.T., 1989: Coralline barium records temporal variability in equatorial Pacific upwelling. Nature 340, 373-376. Levitus S, Burgett R, Boyer TP, 1994: World ocean atlas volume 3: salinity NOAA Atlas NESDIS 3 Washington DC: US Department of Commerce. Linn, L.J., Delaney, M.J., Druffel, E.R.M., 1990: Trace metals in contemporary and seventeenth-century Galapagos coral, records of seasonal and annual variations. Geochim. Cosmochim Acta  54, 387-394. Lough, J.M., Barnes, D.J., McAllister, F.A., 2002: Luminescent lines in corals from the Great Barrier Reef provide special and temporal records of reefs affected by land runoff. Coral Reefs  21, 333-343. Lu, X.X. and Siew, R.Y., 2006: Water discharge and sediment flux changes over the past decades in the Lower Mekong River, possible impacts of the Chinese dams. Hydro. Earth Syst. Sci. 10, 181-195. Mekong River Commission,  2005: "Overview of the Hydrology of the Mekong Basin" Milliman J.D and Meade R.H, 1983: World-wide delivery of river sediment to the oceans. Geology. 91, 1-21. Minle, P.J. and Swart, P.K., 1994: Fibre-optic-based sensing of banded luminescence in corals. Appl. Spectrosc. 48, 1282-1284. Neil, D., Isdale, P., Newman, S., 1995: Coral skeletons as recorders of catchment history, Tully River, North Queensland, Australia. In, Bellwood O, Choat H, Saxena N (eds) Recent advances in marine science and technology 1994, James Cook University, Townsville, 279-287. Shen, GT., Boyle, E.A., Lea, D.W., 1987: Cadmium in corals as a tracer of historical upwelling and industrial fallout. Nature 328, 794-796. Shen, G.T., Campbell, T.M., Dunbar, R.B., Wellington, G.M., Colgan, M.W. and Glynn, P.W., 1991: Paleochemistry of manganese in corals from the Galapagos Islands. Coral Reef. 10, 91-101. Shen, G.T., Cole, J.E., Lea, D.W., Linn, L.J., McConnaughey, T.A., Fairbanks., 1992a: Surface ocean variability at Galapagos from 1936-1982. Calibration of geochemical tracers in corals. Paleoceanography 7, 563-588 Scoffin, T.P., Tudhope, A.W., Brown, B.E., 1989: Fluorescent and skeleton density banding in Prorites lutea form Papua New Guinea and Indonesia. Coral Reefs. 7, 169-178. Scoffin, T.P., Tudhope, A.W., Brown, B.E., Chansang, H., Cheeney, R.F., 1992: Patterns and possible environmental controls of skeletogenesis of Porites lutea, South Thailand. Coral Reefs. 11, 1-11. Smith, T.J. III., Hudson, J.H., Robblee, M.B., Powell, G.V.N., Isdale, P.J., 1989: Freshwater flow from the everglades to Florida Bay, a historical reconstruction based on fluorescent banding in the coral Solenastrea boinrnoni. Bull. Mar. Sci.  44, 147-182. Southon, J., Kashgarian, M., Fontugne, M., Metivier, B., Yim, W.W.S., 2002: Marine reservoir corrections for the Indian ocean and Southeast Asia. Radiocarbon  44, 167-180 Susic, M. and Boto, K.G., 1989: High performance liquid chromatophraphic determination of humic acid in environmental samples at the nanogram level using fluorescence detection. J Chromatogr. 482, 175-187. Susic, M., Boto, K.G., Isdale, P., 1991: Fluorescent humic acid bands in coral skeletons originate from terrestrial runoff. Mar. Chem. 33, 91-104. Tchernia, P., 1980: Descriptive regional oceanography. Pergamon. Oxford University Press, 124-157 Tudhope, A.W., Lea, D.W., Shimmield, G.B., Chicott, C.P., Head, S., 1996: Monsoon climate and Arabian Sea coastal upwelling recorded in massive corals form southern Oman. Palaios. 11, 347-361. Wan, N.J., You, C.F., Li.H.C., Chung, C.H., Li, M.D., 2005: Calibration of Ba/Ca in coral as a proxy of riverine sedimentary ﬂux in south Taiwan. J. Geophys. Res. Abst J. Vol. 7, 01193. World Bank, 2004: Modeled Observations on Development Scenarios in the Lower Mekong Basin. Xue, Z., Lui, P., Ge, Q., 2011: Change in hydrology and sediment delivery of the Mekong River in the last 50 years: connection to damming, monsoon, and ENSO. Earth Surf. Process. Landforms  36, 296-308.